Phytochemical, chromatographic and spectroscopic investigation of Carum copticum seeds and their potential as immunomodulatory agents. (3rd March 2016) - Sonar, Pankaj K.; Singh, Ranjit; Saraf, Shailendra K.
Abstract: Context : Carum copticum seeds have been prescribed in the traditional system of medicine for the treatment of immune disorders, such as asthma and rheumatism. Objective : The objective of this study was to determine immunomodulatory effects of the alcoholic extract and isolated compounds in Swiss albino mice. Materials and methods : Seeds of C. copticum were extracted with 95% v/v alcohol. The immunomodulatory activity of the crude extract was evaluated at the doses of 100, 300, and 500 mg/kg body weight of mice, administered in mice once daily (orally) for 25 days. Volatile oil of C. copticum was isolated by steam distillation and was characterized by GLC and HPLC. Bio-assay-guided fractionation and isolation were carried out and the isolated compounds were characterized and subjected to immunomodulatory activity studies. Results : The n -hexane fraction yielded p -cymene, carvacrol, and α-pinene. The LD50 value of the crude extract was found to be 4500 mg/kg and the values reported for p- cymene, carvacrol, and α-pinene in the literature were 4750, 810, and 3700 mg/kg, respectively. The oral administration of crude extract, n -hexane fraction (HEF), and isolated oils at the dose of 500, 150, and 50 mg/kg body weight, respectively, showed a significant increase in the HA titers, DTH-response, and phagocytosis. The stimulatory effect observed, on humoral and cellular immunity, was compared with the standard (levamisole treated) and control groups. Discussion and conclusion : The results obtained in the study endorse the traditional use of the seeds of C. copticum and the isolated constituents act as immunostimulants.